ANÁLISE DE SENSIBILIDADE DO METAMODELO DA ETIQUETAGEM BRASILEIRA: EDIFICAÇÕES RESIDENCIAIS - Eli, Letícia Gabriela; Mazzaferro, Leonardo; Olinger, Marcelo Salles; Machado, Rayner Maurício e Silva; Melo, Ana Paula; Fossati, Michele; Lamberts, Roberto (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The main objective of this study is to verify the relation between input parameters and thermal load output of a metamodel, based on sensitivity analysis. The study is based on a metamodel developed to assess the thermal load of residential buildings. One residential typology, located in the cities of São Paulo, Belém and Curitiba was adopted. Maximum and minimum values of input data were determined to represent the different combinations among the Brazilian residential buildings. The analysis was carried out by changing one parameter per time, according to a base case pre-determined. The sensitivity analysis was able to describe the influence of each parameter on the metamodel output cooling and heating thermal load. The results show that the metamodel was able to describe the relation between inputs and output parameter. Therefore, it was observed that the influence of each input data depends on the case and climate analyzed.